2021
DOI: 10.3390/membranes11050350
|View full text |Cite
|
Sign up to set email alerts
|

Organic Nanobowls Modified Thin Film Composite Membrane for Enhanced Purification Performance toward Different Water Resources

Abstract: The structure and composition of nanofillers have a significant influence on polyamide nanofiltration (NF) membranes. In this work, an asymmetric organic nanobowl containing a concave cavity was synthesized and incorporated into a polyamide layer to prepare thin film nanocomposite (TFN) membranes via an interfacial polymerization process. Benefiting from the hydrophilicity, hollow cavity and charge property of the compatible organic nanobowls, the separation performance of the developed TFN membrane was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Various technologies have been applied for the treatment of radioactive liquid waste, such as precipitation, adsorption, membrane separation, and other methods [6][7][8][9][10][11]. Membrane methods for separating liquid mixtures have been intensively developed with promising results to resolve various scientific and environmental problems [12][13][14][15][16][17]. However, excellent ions rejection of membranes leads to a reduction in water permeability and vice versa [18], since smaller pore sizes always mean higher selectivity but limited water permeability [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Various technologies have been applied for the treatment of radioactive liquid waste, such as precipitation, adsorption, membrane separation, and other methods [6][7][8][9][10][11]. Membrane methods for separating liquid mixtures have been intensively developed with promising results to resolve various scientific and environmental problems [12][13][14][15][16][17]. However, excellent ions rejection of membranes leads to a reduction in water permeability and vice versa [18], since smaller pore sizes always mean higher selectivity but limited water permeability [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when the salt rejection percentage reaches a high value, the water flux through the membrane decreases. This phenomenon has been seen in several studies [23,[25][26]. Of course, this is one of the main problems of this study.…”
Section: ■ Introductionmentioning
confidence: 49%
“…Many cellulose-based membranes or other biopolymer-based membranes have been modified to improve the membrane performance [18][19][20][21]. Some of these studies showed good performance in terms of rejection of salt which reached above 90% [22][23][24]. On the other hand, when the salt rejection percentage reaches a high value, the water flux through the membrane decreases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Compared to closed hollow structures, the inner and outer surfaces of BNPs can be both exposed to the circumstance, endowing them with high specific surface areas and active sites. [14][15][16][17] Besides, the large opening (>10 nm) on the surface facilitates the facile encapsulation of large-sized cargoes such as nanoparticles and biomacromolecules, for example, DNAs and proteins. [18,19] The fabrication of inorganic BNPs including carbon spheres, [20][21][22] silica nanoparticles, [23] metal oxide nanoparticles, [24] and so forth, is mostly based on the template-assisted method.…”
Section: Introduction Of Bowl-shaped Nanoparticles: Structural Featur...mentioning
confidence: 99%